PENGARUH KUALITAS PRODUK TERHADAP KEPUASAN DAN DAMPAKNYA TERHADAP LOYALITAS KONSUMEN SHAMPO CLEAR - Nirma Kurriwati (Kompetensi (Competence : Journal of Management Studies), 2014)
The quality of products is an important thing that should be pursued by each company if it is to be produced to compete in the market to satisfy the needs and desires of consumers. Increasingly adult consumers mind in considering the quality of a product is chosen, so that requires companies to continually improve their product quality. The level of customer satisfaction is very dependent on the quality of a product. High level of quality that will result in high customer satisfaction. By keeping customer satisfaction will increase survival time relationship with consumers and continue to develop new customers. The purpose of this study was to determine the effect of quality on consumer satisfaction and its impact on consumer loyalty. This study uses primary data collected from the consumer respondents in Surabaya clear shampoo (District of Gubeng) of 100 respondents. Analysis techniques used in this study is paths analisys using AMOS software. The results showed that the quality effect on satisfaction and satisfaction further effect on customer loyalty